Template-free synthesis of highly porous boron nitride: insights into pore network design and impact on gas sorption - Marchesini,S; McGilvery,CM; Bailey,J; Petit,C (ACS Nano, 2017)
Production of biocompatible and stable porous materials, e.g., boron nitride, exhibiting tunable and enhanced porosity is a prerequisite if they are to be employed to address challenges such as drug delivery, molecular separations, or catalysis. However, there is currently very limited understanding of the formation mechanisms of porous boron nitride and the parameters controlling its porosity, which ultimately prevents exploiting the material’s full potential. Herein, we produce boron nitride with high and tunable surface area and micro/mesoporosity via a facile template-free method using multiple readily available N-containing precursors with different thermal decomposition patterns. The gases are gradually released, creating hierarchical pores, high surface areas (>1900 m2/g), and micropore volumes. We use 3D tomography techniques to reconstruct the pore structure, allowing direct visualization of the mesopore network. Additional imaging and analytical tools are employed to characterize the materials from the micro- down to the nanoscale. The CO2 uptake of the materials rivals or surpasses those of commercial benchmarks or other boron nitride materials reported to date (up to 4 times higher), even after pelletizing. Overall, the approach provides a scalable route to porous boron nitride production as well as fundamental insights into the material’s formation, which can be used to design a variety of boron nitride structures.